HUBUNGAN STRESS KERJA DENGAN KELELAHAN KERJA PADA PEKERJA DI PABRIK KELAPA SAWIT TAHUN 2020 - Eva Oktariani; Ahmad Julkandri; Yuharika Pratiwi (LPPM Universitas Abdurrab, 2022)
Occupational fatigue is any condition that is accompanied by decrease in efficiency and endurance at work resulting in work errors, decreased productivity leading to work accidents. Data from the International Labor Organization (ILO) 2013 stated that fatigue causes two million workers to die each year from work accidents. The Ministry of Manpower and Transmigration of the Republic of Indonesia via Director General of Labor Inspection Development in 2012 stated that the average number of workplace accidents in Indonesia is 847 cases per day, in which 36% of the causes are occupational fatigue. There are many factors causing occupational fatigue, including work stress. Work stress can cause emotional reactions, physiological changes and potentially cause occupational fatigue at 61.7%.To investigate the relationship between work stress with occupational fatigue on workers in the POM PT. X Rokan Hulu Tahun 2020. Analytic observational research using cross-sectional approach with 135 samples. This research used a total sampling and analyzed with chi-square test. There is a significant relationship between work stress and occupational fatigue (p- value = 0,000).